'Who controls the past controls the future' Benefits and Challenges of Teaching Young Adult Dystopian Fiction - Luisa Alfes; Joel Guttke; Annetta Carolina Lipari; Eva Wilden (CLELEjournal, 2021)
With the paper Benefits and Challenges of Teaching Young Adult Dystopian Fiction, Alfes Guttke, Lipari & Wilden discuss the enormous potential of dystopian young adult fiction for foreign language learning and present findings of an interview study investigating secondary teachers' experiences with teaching dystopian narratives in German schools.